Purification and Characterization of a Nonenzymatic Neurotoxin from Hippasa partita (Lycosidae) Spider Venom Gland Extract. (13th June 2013) - Nagaraju, S.; Kemparaju, K.
Abstract : India is a habitat for nearly one thousand four hundred forty-seven species of spiders under three hundred and sixty-five genera and sixty families. Our initial survey on toxic bite by spider revealed severe edema, itching, acute pain, and hemorrhage following tissue necrosis, which are the general symptoms of envenomation, but there are no reports of mortality. Significantly, Hippasa partita spider, commonly called "funnel web spider, " which is endemic in hilly regions of the Western Ghats is responsible for envenomation. In this study, a nonenzymatic neurotoxin has been purified from H. partita venom gland extract. Gel filtration and ion exchange chromatography were used to purify the toxin into homogeneity as shown by SDS-PAGE, RP-HPLC, and MALDI-TOF. Neurotoxin is devoid of enzymatic activities but causes intense neurotoxic symptoms. Neurotoxin is found to inhibit the twitch response of sciatic nerve gastrocnemius muscle preparation and is found to be postsynaptic in action. Neurotoxin is devoid of coagulant activity, edema, and hemorrhage and is nonlethal to mice (up to 5 mg/kg body weight). In conclusion, a neurotoxin, which is a principle agent in whole venom responsible for induced neurotoxic symptoms, has been purified and characterized.